Thank you for the opportunity to help you with your question!
just wait a few minut e iwill answer you
we have f(x) = 4x² + 9 and g(x) = x - 2
a) - (f o g)(x) = f(g(x)) = 4(x - 2)² + 9 = 4(x² - 4x + 4) + 9 = 4x² - 16x + 16 + 9 = 4x² - 16x + 25
b) - (f o g)(-1) = 4(-1)²- 16(-1) + 25 = 4 + 16 + 25 = 45
Please just ask if you don't understand
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?